Pengembangan Media E-Book Menggunakan Aplikasi Canva Materi Sistem Pencernaan Manusia Muatan IPA di Kelas V SD Negeri 39 Pontianak Kota - Detia, Nurhafiza; Kresnadi, Hery; Salimi, Asmayani (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
The study you described adopts a research and development approach that combines qualitative and quantitative methods. Theipurpose ofsthe research is to create an E-book using the Canva application. The researchers utilizd three research instruments: observation, interviews, and questionnaires. Preliminary data for the study was gathered through interviews with homeroom teachers of VB classes at SD Negeri 39 Pontianak Kota on Thursday, July 21, 2022. The collected data revealed that the 2013 curriculum was being implemented, and thematic books were used as learning resources. Theme 3, which focuses on thehhuman digestive system, was chosen for the development of the E-book. The research involved fifth-grade studentssat SD Negerik39 Pontianak Kota, and the results indicated that the E-book media created using the Canva application is highly suitable for supporting learning activities in natural science content for Theme 3. The trial activities yielded a feasibility percentage value of 100% in the aspect of language, categorizing it as